“The Serpentine Zone”: A Surgeon's Guide to the Surface Anatomy of the Digital Neurovascular Spiral in Dupuytren's Contracture - Macey, Alistair R. M.; Thomas, Roshin (Journal of Hand and Microsurgery, 2018)
The anatomy of the cords that form in Dupuytren's disease is complicated and a spiral cord is the most challenging variant to address. It displaces the neurovascular bundle toward or beyond the midline and closer to the skin. This article illustrates the surface anatomy of the neurovascular spiral to help surgeons identify this zone of danger that the authors term “the serpentine zone.” Careful dissection in this zone will help avoid iatrogenic digital neurovascular injury.
Keywords: Dupuytren's; spiral cords; surface anatomy